Effects of composite layer plate on modal experimental analysis - Nur Azleen, Abdol Mulok (2013)
The composite plates are basic structural components in aerospace, mechanical and civil industries. This project presents the experimental modal analysis of dynamical behavior of plates made up of woven glass fiber and epoxy matrix in free-free boundary conditions. Two composite plates with different number of layers were analysed. The dynamic characteristics observed are natural frequency and mode shape. The result obtained by experimental modal analysis technique for each structure is then compared with the result obtained by using finite element method (FEM). From the results, the influence of number of layers on flexural natural frequencies is investigated. It shows that as the number of layers increase, the natural frequencies also increases. Comparative study is done between the experimental and the finite element result obtained from ALGOR. From the ODS result, it shows that the dominant mode shape for both four and eight layers composite plates are mode 1. The prediction of dynamical behavior plays an important role for their future design applications.